IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS DARING (WHATSAPP GROUP, GOOGLE CLASSROOM DAN ZOOM MEETING) DI SMP MBS AL AMIN BOJONEGORO - Ibnu Habibi (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2020)
This study aims to describe the implementation of online Islamic education learning at SMP MBS Al Amin Bojonegoro. As a medium for supporting online learning using several online platforms such as Google Clasroom as a web-based virtual classroom interaction medium, and WhatsApp group to support more concise interactions in online classes based on chat platforms and using Zoom as a live streaming media. The research method used is descriptive qualitative so that the utilization of the three digital platforms can be examined in more detail, starting from the weaknesses to the strengths of each. As a result of the research, it shows that online learning has been carried out well, and utilizes various learning media so that PAI learning is more varied and makes students not bored and understands the material presented faster. The obstacles faced were that some students did not have cellphones, the inaccessibility of the Signal and the lack of coordination between students and teachers.